Pengembangan Sumber Daya Porang menjadi Produk Pangan Olahan RT 10 Kelurahan Manggar, Balikpapan Timur - Anggela, Anggela; Nainggolan, Eris Pransiscah; Nabila, Yamaysyah Salma; Ananda, Rahmatia; Asrul, Asrul; Wahyu, Wahyu (Inspirasi: Jurnal Pengabdian Masyarakat, 2024)
The community service activity in RT 10 Kelurahan Manggar, Balikpapan Timur, aimed to enhance the value of porang plants through diversification into processed food products. The program consisted of five stages: Forum Group Discussion (FGD), socialization, demonstration, mentoring, and branding training. The community was taught to process porang into flour, chips, and nuggets, along with marketing training to improve product competitiveness. The provision of a dehydrator supported the sustainability of independent porang processing. The program successfully achieved its objectives by increasing the community’s knowledge and skills in utilizing porang. This initiative created new economic opportunities based on local commodities, serving as a sustainable model for local resource development.